High flow in children with respiratory failure: A randomised controlled pilot trial – A paediatric acute respiratory intervention study. (30th December 2020) - Franklin, Donna; Shellshear, Deborah; Babl, Franz E; Hendrickson, Rikki; Williams, Amanda; Gibbons, Kristen; McEnery, Kate; Kennedy, Melanie; Pham, Trang MT; Acworth, Jason; Levitt, David; Oakley, Ed; et al.
Abstract : Aims: High‐flow is increasingly used in children with acute hypoxaemic respiratory failure (AHRF), despite limited evidence. The primary feasibility endpoint for this pilot‐study was the proportion of treatment failure, secondary outcomes being intensive care unit (ICU) admissions and proportion of patients requiring escalation of care. We measured duration of hospital stay, duration of oxygen therapy and rates of ICU admission. Methods: An open‐labelled randomised controlled trial feasibility design was used in two tertiary children's hospitals in the emergency department and general wards. Children aged 0–16 years with AHRF were randomised (1:1) to either high‐flow or standard‐oxygen. Children on standard‐oxygen received rescue high‐flow in general wards if failure criteria were met. Results: Of 563 randomised, 283 received high‐flow and 280 standard‐oxygen with no adverse events. The proportion of children who failed treatment and receiving escalation of care was 11.7% (32/283 children) on high‐flow and 18.1% (50/280 infants) on standard‐oxygen (odds ratio 0.68, 95% confidence interval 0.38–1.00). In children with obstructive airway disease, 9.7% on high‐flow and 17.4% on standard‐oxygen required escalation (risk‐difference −7.7% percentage points; 95% confidence interval −14.3, −1.1); in children with non‐obstructive disease no difference was observed. Neither difference in ICU admissions nor any difference in length of hospital stay was observed. Sixty percent of children who failed standard‐oxygen responded to rescue high‐flow. Conclusion: High‐flow outside ICU appears to be feasible in children with AHRF and the required proportion of escalation was lower compared to standard‐oxygen. The trial design can be applied in a future large randomised controlled trial.